Proactive Personality and Academic Engagement: The Mediating Effects of Teacher-Student Relationships and Academic Self-Efficacy - Chen, Peiyao; Bao, Chenye; Gao, Qiyang (Frontiers in Psychology, 2021)
Proactive personality provides students with strong competitiveness in academic learning. However, previous research primarily focused on the effects of the big five facets, less attention was paid to proactive personality which shows more incremental validity in learning. The current study aimed to investigate the relationship between proactive personality and academic engagement. The sample consisted of 519 students (245 females, 274 males; Mage = 10.20, SD = 0.891). The study used Mplus 7.0 software to establish structural equation models (SEM). The results showed a significant positive relationship between proactive personality and academic engagement. Teacher-student relationships and academic self-efficacy were found to fully mediate separately between proactive personality and academic engagement. Moreover, the serial mediator model indicated that proactive personality was sequentially related to academic engagement through teacher-student relationships and academic self-efficacy. The implications for learning and teaching are discussed.